Strain-driven composition gradients in nanocrystalline sige - Tzoumanekas, Christos; Kelires, Pantelis C. (My University, 2003)
Strain-driven composition gradients in nanocrystalline SiGe was investigated theoretically. The effect was influenced by the inherent density difference between the crystalline and amorphous components of the material and associated stress fields. It was found that a quantum dot (QD) effect due to composition would be strong for small nanocrystals.
Keywords: Computer simulation; Nanostructured materials